Skilled Birth Attendant and Its Determinants among the Tribal Women of Bangladesh - Karim, Abu Naser MD. Rezaul (Current Women's Health Reviews, 2020)
Background: The indigenous people are socially, linguistically, and scientifically diverse. A global trend leads us to the notion that primitive women are somewhat less privileged than non-tribal mothers around the world. This problem also sounds true in the context of Bangladesh. A competent birth attendant at birth is the most important intervention for pregnant women. However, the use of skilled birth attendants has been widely discriminated among tribal and non-tribal women. Objective: This study assesses SBA acceptance and utilization barriers during childbirth among Bangladesh tribal women. Methods: A quantitative approach was employed, and the data were collected via questionnaires. Descriptive statistics, Chi-square (χ 2) tests and Binary Logistic Regression were used to analyze the frequency, relationship, and to determine tribal women seeking the services of SBA during childbirth. Results: The results showed that the highest prevalence of delivery (66%) among tribal women occurred at home. 46% of the mothers gave birth to their children with the assistance of a skilled birth attendant, of which 12% of them were at home, and 34% were in the hospital. The remaining 54% of mothers gave birth to their babies with the assistance of a traditional midwife. Results also show that socio-economic conditions, education of women, distance from health care facilities, family planning, husbands’ occupation, and media exposure are the key determinants in pursuing SBA. Conclusion: The study revealed a low prevalence of utilizing skilled birth attendance among tribal women of Bangladesh. Hence, upgrading socio-economic conditions and boosting the education levels of tribal women, ensuring easy access to the media, and launching short-term training to train typical birth attendants are the key recommendations for seeking expert birth attendants.
Keywords: traditional (conventional/untrained) birth attendants